(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
This study investigated management of educational resources as predictor of secondary school effectiveness in Calabar Education Zone of Cross River State, Nigeria. The research design adopted in this study was a correlation design. The population and sample of this study were 97 and 50 public secondary school respectively. An instrument for data collection was developed by the researcher and was entitled; “Management of Educational Resource and Secondary School Effectiveness Questionnaire (MERSSEQ)” To establish the reliability of the instrument, the researchers administered a test 50 teachers who were not involved in the study. The reliability indices of the instrument ranged from 0.82 to 0.88, As such, the instrument was justified suitable to be used for data collection. The data collected were coded and analyzed using simple linear regression. The result of the analysis indicated that management of educational resources in terms of physical and human resources significantly predict secondary school effectiveness in such areas as monitoring of students’ academic progress and conducive teaching and learning environment Calabar Education Zone of Cross River State. Based on the results of the analysis, one of the recommendations was that, principals of public secondary schools should ensure improvement in the management of their respective schools’ physical resources in order to enhance secondary school effectiveness in the area of provision conducive learning environment for effective teaching and learning processes.